The Impact of Paternal and Maternal Parenting Styles on Alexithymia - Moormann, Peter Paul; Bermond, Bob; de Groot, Manon; Syahid, Achmad; Lagoudaki, Kalliopi (Tazkiya Journal of Psychology, 2024)
Rogers stressed the impact of Conditional Regard (CR) towards the child in the development of neurotic anxiety. Miller noted that disorders in affect regulation relate to family atmospheres where the child is not allowed to express negative emotions. However, studies on the impact of paternal and maternal parenting styles lacking emotional warmth (EW) on the development of alexithymia in adulthood remain scarce. Therefore, The Bermond-Vorst Alexithymia Questionnaire (BVAQ) and the Leiden Parent-Child Interaction Questionnaire (LPCIQ-R) were administered to 152 male and female bachelor psychology students from 18 to 60 years of age at Leiden University. The results demonstrate that: 1) Both paternal and maternal parenting styles lacking EW induced significantly higher Alexithymia Total scores; 2) Fathers lacking EW induced significantly higher scores on Cognitive Alexithymia, while mothers lacking EW induced significantly higher scores on Affective Alexithymia; 3) Both CR fathers and CR mothers induced difficulties with Identifying emotions; 4) CR fathers induced difficulties with Verbalizing emotions, while 5) Indifferent mothers induced difficulties with Emotionalizing. The results above not only support Rogers’ view on the devastating affect of CR on emotion regulation, but empasize the different impact of paternal and maternal roles on the development of alexithymia features as well. In the past mothers were seen as the primary caretakers and consequently mothers were blamed for the child’s mental health problems. However, our results show that Cognitive Alexithymia, known for its association with mental illness is induced by fathers lacking EW. In contrast Affective alexithymia, associated with on the one hand stress resistance, and on the other hand lack of empathy and creativity, turned out to be induced by mothers lacking EW. Hence, with the growing active role of fathers in child rearing it is unfair to blame mothers for the child’s mental problems without prior investigations of parenting styles lacking EW.